Kondisi Sosial Ekonomi dan Nilai Tukar Nelayan (NTN) Bouke Ami di Pelabuhan Perikanan Nusantara (PPN) Muara Angke, Jakarta Utara - Raihan Sulaiman Payapo; I Wayan Restu; Suprabadevi Ayumayasari Saraswati; I Ketut Wija Negara (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Fishermen are an essential group in supporting national food security; however, their lives are still characterized by various social and economic challenges, such as unstable income, low education levels, and high household expenditure burdens. This research aims to provide an overview of the socio-economic conditions and welfare of Bouke Ami fishermen in the Nusantara Fisheries Port (PPN) Muara Angke, North Jakarta, through the Fishermen’s Exchange Rate (NTN) and Fishermen’s Exchange Rate Index (iNTN). The study was conducted in May–June 2025 using a descriptive method with quantitative and qualitative approaches. Data collection techniques included observation, interviews, and questionnaires distributed to 100 Bouke Ami crew members (ABK). The results showed that the majority of crew members were aged 30–39 years, had completed only junior high school education, received health services through community health centers (puskesmas), had three family dependents, and most lived in their own homes. The average total monthly income of Rp5.733.500 is considered high as it exceeds the 2025 DKI Jakarta minimum wage (UMP) of Rp5.367.381. Meanwhile, the average total expenditure of Rp5.396.761 remains below income, indicating manageable household finances. The NTN value was 1,06 in April and 1,07 in May, resulting in an iNTN of 101%, indicating that Bouke Ami fishermen in PPN Muara Angke, North Jakarta, are at a level of economic welfare classified as prosperous with slight improvement. This increase reflects a modest rise in fishermen’s purchasing power between the two months and can serve as basis for formulating policies aimed at empowering coastal fishermen.